Evaluación de las variables del comportamiento organizacional y su incidencia en el desempeño laboral en la fábrica SAILOR PAINT S.A. - Cobeña Bravo, Merly Lourdes (2022)
The objective of the research was to evaluate the variables of the organizational behavior of the employees of the Sailor Paint S.A. paint factory in Guayaquil city and its impact on job performance. To determine the variables to be evaluated, a group of experts was selected to choose the appropriate variables to be evaluated in the investigation by means of the DELPHI method. Afterwards, the outline of the evaluation instruments for the identification of the indicators was made, this was done with the help of the bibliographic review. Once the indicators were obtained, they were applied and proceeded with the respective analysis and statistical processing of the information obtained with the application of the instrument. And finally, we proceeded to solve the problems found in the company, making a proposal for an improvement plan that consisted of corrective and preventive actions that would help the company to increase the level of business competitiveness.